Intratumoral Co-Administration of Oncolytic Newcastle Disease Virus and Bacterial Hyaluronidase Enhances Virus Potency in Tumor Models - Hasanain Sahib Salih (Journal of Global Pharma Technology, 2018)
Purpose: Bacterial hyaluronidase in co delivery evaluation effect with oncolytic Newcastle Disease Virus to determine spreading of the virus throughout Adenocarcinoma tumors Models in mice, and evaluate the reduction in tumor mass by efficacy of co delivery injection in tumor models. This study aimed to define the success of Combination effect between bacterial origin hyaluronidase and Newcastle Disease Virus and compare the invasion of this combination versus treatment with hyaluronidase enzyme or with oncolytic Newcastle disease virus only.Experimental Design:Newcastle disease virus (NDV) titration 6.3x105 injected in combined dose with 200 international unit (IU)  bacterial origin hyaluronidase to provide a mass invasion efficiency and spread of Newcastle disease virus within tumors that detected through the measurement of growth inhibition of tumor mass and  immunofluorescence detection assay. The experiment performed in vivo in mice bearing AMN3 tumor cell line model. Conclusion: The data presented in this study show that combination treatment of solid tumors with an NDV and bacterial origin hyaluronidase significantly improves spread of virus through the tumor mass, resulting in prolonged survival of the tumor-bearing animals and in vivo tumor mass reduction without increasing the metastatic potential. Thus, this combination of NDV and hyaluronidase may offer a novel and promising therapy for the treatment of patients with cancer.Keyword: NDV (Newcastle Disease Virus), HA (Hyaluronic Acid), AMN3 (Ahmed Murtatha Nahi 2003 Cell Line), ECM (Extra Cellular Matrix).